A preliminary exploration of the Challenging Behaviour Perception Questionnaire: A measure of parental cognitions about challenging behaviour. Issue 2 (3rd April 2018) - Rose, John; Nelson, Lisa
ABSTRACT: Background Although there has been interest in the influence of cognitions on the relationship between challenging behaviour and maternal wellbeing, there is an absence of measures to specifically examine parents' perceptions of challenging behaviour. The psychometric properties of the Challenging Behaviour Perception Questionnaire (CBPQ; Williams, R. J., & Rose, J. L. [2007]. The development of a questionnaire to assess the perceptions of care staff towards people with intellectual disabilities who display challenging behaviour. Journal of Intellectual Disabilities, 11, 197–211) were investigated to assess its applicability to mothers. Method Forty-six mothers of children and young adults with intellectual disability completed questionnaires regarding their child's challenging behaviour, maternal cognitions, and stress. A subsample of participants completed the CBPQ 2 weeks later. Results Examination of the psychometric properties of the CBPQ resulted in a 24-item measure with 6 subscales. Coefficients at subscale level ranged from .70 to .85 for internal reliability and .39 to .93 for test–retest reliability. Evidence of concurrent validity was also found. Conclusions The CBPQ is a promising measure of perceptions of challenging behaviour and could be usefully employed in subsequent studies.